Comparison of clinical, radiographic, histometric measurements following treatment with guided tissue regeneration or enamel matrix proteins in human periodontal defects - Windisch, Péter; Sculean, Anton; Klein, Filip; Tóth, Vilmos; Gera, István; Reich, Elmar; Eickholz, Peter (Journal of periodontology, 2002)
The purpose of this study was to compare the clinical and radiographic parameters with the histometric findings following 2 different regenerative procedures in humans.
Gesehen am 16.03.2021